ANALISIS KAPASITAS SIMPANG TUGU GADING AKIBAT BANGKITAN PERGERAKAN DI PASAR ALOK MAUMERE, KABUPATEN SIKKA: Capacity Analysis of Tugu Gading Intersection Due the Surge in Movement at Alok Market Maumere, Sikka Regency - Blasius Retno Laja; Yono Putra; Alfrendo Satriawan Kabupung (Program Studi Teknik Sipil, 2025)
This study aims to analyze the capacity of the Tugu Gading intersection as an impact of traffic generation from Alok Market, Sikka Regency. Trading activities in the market significantly increase traffic flow, especially during peak hours, and affect the overall performance of the intersection. The research method refers to the Indonesian Highway Capacity Manual (MKJI, 1997) to calculate traffic volume, degree of saturation, delay, and level of service. Data were collected through field surveys by recording vehicle volumes based on type classification and observing the geometric conditions of the intersection. The analysis results show that traffic volumes during peak hours exceed the intersection’s ideal capacity, causing the degree of saturation to reach a high category. This condition leads to longer average delays and a decrease in the intersection’s level of service to poor category. The findings indicate that Alok Market contributes significantly to traffic congestion at the Tugu Gading intersection. Recommendations include traffic management improvements, road widening, and better control of parking activities around the market to enhance traffic flow and reduce delays. This research is expected to serve as a valuable reference for local governments in planning transportation policies and spatial arrangements for market areas.